(untitled) (City: History, Culture, Society, 2020)
This article is about the problem of the historical topography of the downtown of Bakhchisarai -Hansaray. It was the centre of formation of the medieval city and the capital of the Crimean Khanate. A popular belief is that Hansaray is, in one sense, a copy and development of the idea of a medieval Eastern Palace (videlicet, the Top Cap in Istanbul) and dominates in historiography. The study of kırımlı cultural and historical heritage remains at a very low level as a result of permanent genocide by Russia empire in the XIX-XX centuries. This led to the development of a distorted picture of the historical and scientific understanding of cultural heritage. Great and significant monuments, even scientific memory about them, have disappeared from the cultural and historical landscape. Mehmed IV Geray baths is an example of this. The actual location of the monument with the help of archaeological geolocation method has been determined in this article. This discovery and interpretation, as an important part of the palatial part of the city development, gives a different look at the whole complex of Hansaray. The Khan’s Palace is the centre of the city in contradistinction from the Oriental palaces. Quarters of socially important structures formed around it (one of them was Mohammed IV Giray’s baths). After that city development transforms into civic blocks with town mansions, mosques and other public buildings.